2015
DOI: 10.1016/j.bbrc.2015.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of episomal vectors into primary cells by means of commercial transfection reagents

Abstract: Although episomal vectors are commonly transported into cells by electroporation, a number of electroporation-derived problems have led to the search for alternative transfection protocols, such as the use of transfection reagents, which are inexpensive and easy to handle. Polyplex-mediated transport of episomal vectors into the cytoplasm has been conducted successfully in immortalized cell lines, but no report exists of successful transfection of primary cells using this method. Accordingly, we sought to opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Illkirch, France) according to the manufacturer's protocols. 20 Control Non-target siRNA and TAOK1 on-target siRNA were obtained from Dharmacon (Thermo Fisher Scientific, Waltham, MA, USA). siRNA were transfected into HeLa cells with Lipofectamine RNAiMAX Basic information of human samples about non-IBD control and UC patients from Xinhua hospital.…”
Section: Human Samplesmentioning
confidence: 99%
“…Illkirch, France) according to the manufacturer's protocols. 20 Control Non-target siRNA and TAOK1 on-target siRNA were obtained from Dharmacon (Thermo Fisher Scientific, Waltham, MA, USA). siRNA were transfected into HeLa cells with Lipofectamine RNAiMAX Basic information of human samples about non-IBD control and UC patients from Xinhua hospital.…”
Section: Human Samplesmentioning
confidence: 99%
“…As known, Lipofectamine™ 2000 contain lipid subunits that can form liposomes in an aqueous environment, composed of cationic phospholipids (dioleoylpropyl trimethyl ammonium chloride/dioleoylphosphatidylethanola mine =1/1), whose transfection efficacy for gene therapeutics has been well proved. 26,27 The transfection ability of fc-LPs was not inferior to that of Lipofectamine™ 2000 at all. Besides the low toxicity and cost, the high transfection efficacy rendered fc-LPs rather promising as nonviral vectors for HIF-1α siRNA delivery.…”
Section: Edc N-(3-dimethylaminopropyl)-n′-ethylcarbodiimidementioning
confidence: 87%
“…A previous study demonstrated that the promoter activity is dependent on the cell type [40]. Although CMV promoters are commonly used for the high expression of transgenes in mammalian cells [41,42], they may be inappropriate promoters for strong expression in primary cells. The EF-1α promoter can drive transgene expression in primary cells, but the expression level needs to be further improved.…”
Section: Discussionmentioning
confidence: 99%